Finite Element Analysis of Wave Barriers Used to Reduce Train Induced Vibrations - Al-Jubair, Haider S.; Ali, Jaafar K.; Ajel, Hasan A. (Basrah Journal for Engineering Sciences, 2021)
The finite element method is used to simulate the soil vibration behavior due to the Basrah-Baghdad passenger train and its effect on a targeted building in the Al-Ma'qal quarter, Basrah governorate. Three-dimensional dynamic elastic analyses are performed to calculate the particle velocities for a train speed of 120 km/hr. The effectiveness of screening using active (10 m long) open trench barriers with variable depth (2 m - 5 m) and width (0.4 m - 0.8 m), is being studied. For a given trench width (0.4 m), the results of the parametric study revealed a considerable effect of trench depth where the screening capability near the trench is increased by (10.4 %, 26.1 %, 36.3 %) due to a (50 %, 100 %, 150 %) increase in depth. The results are less sensitive to the variation in trench width. The screening capability of a double open (0.4 m × 10 m × 2 m) trench system was also investigated, where a mitigation improvement of (36.4 %) was achieved. The vibration mitigation using single and double trench systems, filled with (40 %) rubber content mixture, was also analyzed. It is concluded that using the additional passive trench increases the mitigation of the single system by around 19.1 %. An important finding is that the (40 % rubber + 60 % native cohesive soil) mixture proved to be a good filling material, since the infilled-trench systems produced comparable screening ratios to the open systems, where (97.7 %) and (85.4 %) were accomplished for the single and double systems, respectively.